Feminism in song of jineman kenya ndesa laras slendro pathet sanga - Sukesi Rahayu; Katrhryn Emerson; Phakkharawat Sittiprapaporn (Institut Seni Indonesia Surakarta, 2021)
AbstractFeminism in Sukesi Rahayu's Jineman Kenya Ndesa laras slendro pathet sanga is a study that reviews feminist discourses on the creation of gamelan music based on the issues of gender equality between women and men. The purpose of this research is to prove and show that the creation of Javanese karawitan is not only based on male paradigm domination, but women also have a role in speaking out about feminism through karawitan works. The research methodology used is descriptive qualitative by positioning the object of study as the primary focus and writings on feminism as supporting sources. The results of this study indicate that in Sukesi Rahayu's Jineman Kenya Ndesa Slendro Sanga, there is feminist content, namely an attempt to elevate the dignity of women, which in this case is sindhen, within the scope of Javanese art culture as well as women in general.Keywords: Feminism; Sindhenan; Javanese culture